CONTRIBUTION A L’ÉTUDE HYDROLOGIQUE DANS LES MONTS DE SAIDA - Dj., Anteur; H., Remmas; A ., Labani .; Z., Regagba (European Scientific Journal, ESJ, 2015)
If the evaluation of resources out of surface water is very useful with an aim of their planning, their installation, it is useful to know the hydrological reactions of the tank with respect to the conditions of food. It is one of the essential parameters in the overall estimate of the water resources. TheMounts of Saida, by their geographical location and his lithological constitution, plays a very important part in regional hydrology. It is in this mountainous solid mass that the karstic main sources of the zone occur; Ain Zerga, Ain Tifrit,Ain Soltane and Ain Balloul from which Tifrit wadi,wadi Sidi Mimoun and Saida wadi leave. The Flows of Different wadi and its affluents and the sources are defined starting from the statistical analysis of the chronicles of the daily medium flows. The common period of the observations of surface water 35 years east between September 1972 and August 2007.